Global Alignment of Carbon Nanotubes via High Precision Microfluidic Dead‐End Filtration. (29th October 2021) - Rust, Christian; Li, Han; Gordeev, Georgy; Spari, Manuel; Guttmann, Markus; Jin, Qihao; Reich, Stephanie; Flavel, Benjamin S.
Abstract: Single wall carbon nanotubes (SWCNTs) dispersed by negatively charged sodium deoxycholate (DOC) or positively charged cetrimonium bromide (CTAB) are shown to assemble into aligned films (3.8 cm 2 ) on polycarbonate membranes by slow flow dead‐end filtration. Global alignment ( S 2D max  ≈ 0.85) is obtained on both pristine polyvinylpyrrolidone (PVP) coated membranes and those with an intentional 150–600 nm groove pattern from hot embossing. In all cases, a custom microfluidic setup capable of precise control and measurement of the volume rate, transmembrane pressure, and the filtration resistance is used to follow SWCNT film formation. Conditions associated with the formation of SWCNT crystallites or their global alignment are identified and these are discussed in terms of membrane fouling and the interaction potential between the surface of the membrane and nanotubes. SWCNT alignment is characterized by cross‐polarized microscopy, atomic force microscopy, scanning electron microscopy (SEM), and Raman spectroscopy. Abstract : A custom microfluidic setup capable of precise control and measurement of the volume rate, transmembrane pressure, and resistance is used to probe the mechanism behind the global alignment of carbon nanotubes by dead end filtration. Alignment is shown for both positively and negatively charged carbon nanotubes and on membranes with and without surface texturing.